Modelo para análise da maturidade de sistemas de gestão da qualidade em redes horizontais de empresas - Pereira, Rafael da Silva (2015)
This study aimed to propose a model that may assist businesses owned by horizontal networks of companies to identify and improve the level of maturity in the quality management system (QMS). For this, a literature review was conducted through a different methodology of research and selection of scientific papers, being analyzed all scientific papers published from January 1994 to June 2013 and made available on the Journals Portal CAPES, forming a portfolio specialized bibliographic to the proposition of the methods, tools and models for identification and improvement of the proposition level of maturity in the QMS. This portfolio has the identification of variables that substantiate the identification of tool maturity level, as well as in the identification of quality management tools that was based on the proposition of the techniques that helps these companies in the search for maximum level in QMS. So with that base, proposed a model that allows the construction of a structured basis to evaluate the performance of evolutionary levels of quality management in horizontal networks. Finally, the model was applied to a Productive Cluster of the metal-mechanic sector, situated in the city of Ponta Grossa-PR. The main results obtained, a model with a methodological framework for implementing simple and objective, allowing its application in any regional, State, national typology and in isolated companies, assigning to the high level of model applicability. Besides this, the model has considerable flexibility to adapt, being possible the insertion or removal of variables in the analysis tool maturity level. The model allows that each company analyze critically what tools will implement from the economic feasibility and strategy of the company.